NATIONAL PHYSICAL EDUCATION TRADITIONS: GENDER ROLES CONSTRUCTING PRIORITIES - Senuk, Z.V.; Yagodin, V.V.; Novakovsky, S.V.; Krutko, I.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the National physical education history and traditions in the gender roles construction contexts of indigenous cultures. Methods and structure of the study. We used, for the purposes of the study, the following methods: analysis of the relevant theoretical study reports (in psychology, pedagogy and social science); analysis of the relevant literature, particularly studies of the folk epics, ethnic physical practices, National physical education traditions; and made an analytical revision of the relevant sociological research findings. Results and conclusion. We found the most challenging national physical education systems in the northern ethnic groups living in severe climates – including the Siberian, Far Northern and Far Eastern indigenous groups, plus the nations with long and hard history of military conflicts, such as those in the Caucasus, Central Asia and North America. It is quite typical for these indigenous groups to develop rather special and purposeful National physical education systems with authoritative physical education mentors nominated by the communities for the strictly controlled, comprehensive and systemic trainings. Studies of such traditional National physical education systems in different historical periods find the same physical education principle in every ethnic group.